Effect of different sugars on the freezing characteristics of Kyoho grape - Cao, Xuehui; Zhang, Fangfang; Zhu, Danshi; Zhao, Dongyu; Liu, Liping (Journal of texture studies, 2018)
The aim of this work was to analyze the effect of different osmotic dehydration (OD) processes (sucrose, trehalose, glucose, and lactose) as a pretreatment for grape before exposure to freezing. The osmotic treatment had less effect on blueberry moisture content among different sugars. Impregnation with sugars decreases the freezing time of grapes, compared to untreated grapes. Trehalose and lactose had a remarkable effect on shortening the time for grapes to pass the zone of maximum crystallization of ice. It was concluded that drip loss and electrolyte permeability of cell membranes decreased and the soluble solids content increased after OD treatment. In addition, the firmness and L* values of trehalose‐treated grapes were significantly higher than those of other treatments (p < .05). In summary, osmosis with a carbohydrate solution not only increased the freezing rate but improved quality characteristics of grapes after freezing and thawing. Practical applications Grapes are subject to freezing damage during storage, including significant water loss, berry softening, off flavor occurrence, which reduce the commodity and consumption of grapes. OD can improve the freezing rate by reducing the moisture content in the raw material and reducing the impact of freezing on the quality of fruits and vegetables, which may be beneficial to the process of freezing grapes.